ANALYSIS OF CAMPING GROUND TOURISM FEATURES ON THE WATU GAMBIR PARK WEBSITE - Hartatik Hartatik (Yayasan Education and Social Center, 2022)
Over time the world of digitization has progressed rapidly. Utilizing digitalization during the Covid-19 pandemic can help various sectors of the economy and can make it easier for customers to find out related information. It has a variety of facilities that can be enjoyed by visitors, such as flower garden and lake tours, river tubing, boats, lodging and camping round reservations. Through this, the tourist village of Watu Gambir implements the use of digitalization by using a web application to reserve camping grounds for potential visitors. In the existing Watu Gambir tourism village web application, we conducted research with a descriptive analysis method to find out the benefits of the Watu Gambir tourist village web application for camping ground reservations. From the results of the research method carried out, the average respondent argues that the information provided by the Watu Gambir Park website is still incomplete